Transições - caminhos para um território urbano sustentável - Rodrigues, Adriana Brandt (2019)
The City Statute, in its article 2, as the first guideline, highlights the "guarantee of the right to sustainable cities, understood as the right to urban land, housing, environmental sanitation, urban infrastructure, transport and public services, work and leisure, for present and future generations" (BRASIL, 2001). In the same direction, in 2015, the United Nations proposed the Sustainable Development Goals - SDG. In this document, special attention is given, in the provisions of Goal 11, to the need to "make cities and human settlements inclusive, safe, resilient and sustainable" (UN, 2015). Still on this track, in 2016, UN Habitat published the New Urban Agenda, recognizing that cities are protagonists in a world that is intended to be sustainable, being part of the solution and not the problem. This set of devices reinforces the urgency of a sustainable urban territory. However, what we see is that the challenges to achieving urban sustainability persist, even in an economically thriving region whose cities are small and medium-sized, as is the case of the Western Region of Paraná. The same City Statute states that urban planning is the responsibility of the public authorities. Thus, the hypothesis of investing in the strengthening of professionals who work with urban planning and sustainability will be tested, having as principles of this strengthening of intellectual capital thedevelopment of both technical and transversal competencies, using as a tool a training process whose methodology is an inductive pedagogy, aimed at the transformation of the territory and sustainable development. To this end, this training should provide innovations (technical and methodological), prospective vision, incentives to partnerships, territorial locus (the city inserted in its territory) and should be oriented to the delivery of products, as an effective and sustainable way to increase the quality of life of the population of a city. The objective of this work is, then, to analyze if the analyzed training has proven to be an effective tool to strengthen the intellectual capital of the Western Region, making use of the development of technical and transversal skills for sustainable development, in order to contribute to the filling of existing gaps in urban planning in the municipalities of the Region and, with this, contribute, in the long term, with the improvement of the quality of life of the West and Tri-national population.